Enhancing the attractiveness of public library spaces a case study of selected branches in Rzeszów - Martyka Anna; Figurska-Dudek Joanna; Pásztor Peter; Kuśmierska Martyna; Sorek Natalia; Owsiak Joanna (Technical Transactions)
Municipal public libraries are part of the public function of the city, playing an important role in community life and being a place of integration. Libraries are used by a large group of people of all ages, but many do not realise the potential of these places due to limited access and use. The basis for this article was the participation of the ZARYS Architecture Club in a UNICEF project in cooperation with the Municipal Public Library in Rzeszów. The architecture students carried out an inventory as a prelude to designing new interiors for selected libraries in order to improve their functioning. The study can serve as a basis for further research and transformation of library spaces in Rzeszów.